Soil-transmitted helminthiasis in four districts in Bangladesh: household cluster surveys of prevalence and intervention status - Stacy L. Davlin; Alexander H. Jones; Sanya Tahmina; Abdullah Al Kawsar; Anand Joshi; Sazid I. Zaman; Muhammad M. Rahman; Bozena M. Morawski; Michael S. Deming; Rubina Imtiaz; Mohammad J. Karim (BMC, 2020)
Abstract Background In 2016, after 8 years of twice-annual nationwide preventive chemotherapy (PC) administration to school-age children (SAC), the Bangladesh Ministry of Health & Family Welfare (MOHFW) sought improved impact and intervention monitoring data to assess progress toward the newly adopted goal of eliminating soil-transmitted helminthiasis (STH) as a public health problem. Methods We surveyed four Bangladeshi districts between August and October 2017. We conducted a multi-stage, cluster-sample, household survey which produced equal-probability samples for preschool-age children (PSAC; 1-4 years), SAC (5-14 years), and adults (≥ 15 years). Standardized questionnaires were administered, using Android-based smart phones running an Open Data Kit application. Stool samples were collected and testing for STH prevalence and infection intensity used the Kato-Katz technique. Results In all, 4318 stool samples were collected from 7164 participants. Estimates of STH prevalence by risk group in three of the four surveyed districts ranged from 3.4 to 5.0%, all with upper, 1-sided 95% confidence limits < 10%. However, STH prevalence estimates in Sirajganj District ranged from 23.4 to 29.1%. Infections in that district were spatially focal; four of the 30 survey clusters had > 50% prevalence in at least one risk group. Among all tested specimens, Ascaris lumbricoides was the most common STH parasite [8.2% (n = 352)], followed by Trichuris trichiura [0.9% (n = 37)], and hookworm [0.6% (n = 27)]. In each district, PC coverage among SAC was above the 75% program target but did not exceed 45% among PSAC in any district. Improved sanitation at home, school, or work was over 90% in all districts. Conclusions In the three low-prevalence districts, the MOHFW is considering decreasing the frequency of mass drug administration, per World Health Organization (WHO) guidelines. Also, the MOHFW will focus programmatic resources and supervisory efforts on Sirajganj District. Despite considering WHO guidance, the MOHFW will not expand PC administration to women of reproductive age partly due to the low prevalence of hookworm and T. trichiura, the STH parasites that contribute most to morbidity in that risk group. Data collected from surveys such as ours would help effectively guide future STH control efforts in Bangladesh and elsewhere.